Implementasi Struktur Tiga Babak dalam Penulisan Naskah pada Video Feature “Jejak Rasa: Akar dari Tanah Priangan” - Fazila Safia Utomo; Diya Mirzha Rusyanto; Rinda Aunillah Sirait; Kurnia Lucky Fadillah (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2026)
This study aims to explain the implementation of the three-act structure in scriptwriting for the feature video entitled “Jejak Rasa: Akar dari Tanah Priangan.” The background of this research is based on the tendency of audiovisual representations of cassava that remain partial, focusing only on either traditional or modern aspects without integrating both into a cohesive narrative. This study employs a qualitative approach based on creative practice, where the author acts as a scriptwriter responsible for designing the narrative flow using the three-act structure: set up, confrontation, and resolution. The production process consists of three stages: pre-production, production, and post-production, involving literature research, field observation, interviews with key informants, and the development of visual and audio narratives. The findings indicate that the implementation of the three-act structure successfully creates a systematic narrative that integrates historical, cultural, and modern dimensions of cassava transformation. This structure also effectively builds a coherent dramatic flow and enhances audience emotional engagement. The implications of this study are expected to provide references for academics and practitioners in developing research-based audiovisual scriptwriting, particularly in the context of local culture and gastronomy.